Analysis of transformer and CNN based approaches for classifying renal abnormality from image data - Reza, S. M. Mushfiq; Hasnath, Abu Bakar; Roy, Ankita; Rahman, Amreen; Faruk, Abdullah Bin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.